2017
DOI: 10.1002/lary.26791
|View full text |Cite
|
Sign up to set email alerts
|

Relating quality of life to outcomes and predictors in adult cochlear implant users: Are we measuring the right things?

Abstract: 4. Laryngoscope, 128:959-966, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 32 publications
6
29
1
3
Order By: Relevance
“…In addition, as difficulty with intelligibility is most pronounced in noisy surroundings, the hearing impaired may avoid these situations. This finding is in accordance with the results of a previous study ( 27 ) which also found the highest correlations between patient-reported benefit, here assessed with the Nijmegen Cochlear Implant Questionnaire, and sentence comprehension in quiet. Further, it suggests that the common clinical practice of assessing CI-aided speech comprehension in quiet is a valid approach.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, as difficulty with intelligibility is most pronounced in noisy surroundings, the hearing impaired may avoid these situations. This finding is in accordance with the results of a previous study ( 27 ) which also found the highest correlations between patient-reported benefit, here assessed with the Nijmegen Cochlear Implant Questionnaire, and sentence comprehension in quiet. Further, it suggests that the common clinical practice of assessing CI-aided speech comprehension in quiet is a valid approach.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies, the total NCIQ score did not correlate with auditory measures and may not best capture CI Second, we predicted that the auditory measures used in this study would demonstrate stronger correlations with NCIQ scores than traditional clinical measures. Relations between auditory outcome measures and subdomain QOL scores were stronger than those in previous work (Olze et al, 2012 18 ; Capretta and Moberly, 2016 2 ; Moberly et al, 2018 15 ). This finding may be a result of the incorporation of speech recognition tests that could be considered more "real life" by providing greater talker variabiity and greater linguistic complexity that relate better to real-world communication environments.…”
Section: Discussioncontrasting
confidence: 62%
“…The CID W-22 word list was used in this study as previous studies have demonstrated a broad range of word recognition performance with minimal ceiling and floor effects in the adult CI population using this measure. This task was also chosen to maintain consistency in methods between the present study and our previously completed study involving many of the same participants (Moberly et al, 2018 15 ).…”
Section: Auditory and Audiovisual Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Humes [2003] and Humes et al [2003] showed no correlation in a similar sample as well as in a large meta-analysis. In addition, absent to low correlations between patient self-report and speech recognition have been reported in cochlear implant users [Brendel et al, 2014;McRackan et al, 2016;Ramakers et al, 2017;McRackan et al, 2018a;McRackan et al, 2018b;Moberly et al, 2018]. Together, these data support the added value of PROMs as an independent measure of patient-perceived benefit from hearing interventions.…”
Section: Discussionmentioning
confidence: 74%